People, resources and food in sub-saharan Africa - Bunting, Hugh (Technical Centre for Agricultural and Rural Cooperation, 1988)
Hugh Bunting Professor Hugh Bunting of Reading University, UK, has been Professor of Agricultural Botany (1956-1973), and Professor of Agricultural Development Overseas (1974-1982). Taken as a whole, sub-Saharan Africa has the potential resources...